UPAYA PENINGKATAN KESEHATAN SISWA SD NEGERI 2 SENGGIGI MELALUI PROGRAM : “KENALI MAKANMU, JAGA KESEHATANMU” - Arhya Putra, Made Raditya; Octora, Metta; Abdiman, I Made Tobias; Putri, Atina Rizki; Hazaa, Saskia Safarinaa; Farras, Afif; Sholihatin, Illiyani; Nurhaliza, Siti; Kadarisma, Shofia; Putra, Yusril Sani Riandika; Ginuluh, Gintis Dhimar; Hayaza, Safira Said; Retnaningsih, Ekawaty; Mujahid, Sabila Izzatina Azmy; Makbul, Ini Hidayat; Hardyningrat, Baiq Inna Dwi; Kirana, Devi Chandra; Nugraha, Kadek Nandita; Ishlahi, Salsabila Dinda Nuril; Yahya, Najla Aulia; Amanullah, Mohammad Sany Rosafi (Universitas Mataram, 2024)
Snacks in the school environment have an important role in fulfilling good nutrition and nutrition for elementary school students. Currently, there are still many traders who do not pay attention to the snacks sold both in terms of health, composition, and hygiene. Based on data from BPOM or the Food and Drug Supervisory Agency, around 39.96% of snacks that are not eligible for consumption are spread throughout Indonesia. This shows how important it is for school students to pay more attention to their health in choosing snacks in the school area. This also underlies the conduct of counseling on healthy food and snacks in the elementary school environment in the Senggigi area, West Lombok Regency as a target elementary school from the Faculty of Medicine, University of Mataram. The counseling was carried out for grade 1 and 2 students of SDN 2 Senggigi and was carried out on Friday, September 1, 2023 at 09.00 – 10.00 WITA. Counseling activities include providing counseling materials about healthy snacks, singing healthy snack songs, pre and post-tests, healthy snack games, and ending with giving fruits to students as participants in counseling. Furthermore, pre and post-test result data was processed using the SPSS application and there was a change in the average value of students' knowledge before and after the delivery of healthy snack counseling materials.